Relationship of blood lactate accumulation to stroke rate and distance per stroke in top female swimmers - Weiss, M.; Reischle, K.; Bouws, N.; Simon, G.; Weicker, H. (Swimming Science V, 1988)
Swimming velocity (v) is the function of stroke rate (S} and distance per stroke (d/5). As shown by CrC).ig and Pendergast (1979) stroke rate is a nonlinear function of v: When S is increased above the optimal point, v decreases. The reason for this nonlinear function between S and v is a shortening of d/5. Energy demand (E) in swimming der.ends on efficiency (eff.), body drag (db), and v; therefore Eisa function of 5 and d/5. The total energy delivery is the sum of aerobic metabolism (V02) and anaerobic metabolism (glycolysis leading to lactate production and the breakdown of phosphates, especially creatin phosphate [CP]). When swimming longer than 20 s under steady state conditions, CP is constant. At low speeds, lactate produced can be eliminated and blood lactate remains constant, but at high speeds above 70 or 80% V02max, blood lactate accumulates (anaerobic threshold onset of blood lactate accumulation [OBLAJ) as a function of S and d/S. Furthermore, efficiency during constant work depends on frequency in all cyclic movements. This has been shown for bicycle ergometers (Stegemann, Ulmer, & Heinrich, 1968), rowing (Raatz & Krause, 1977), and running (Cavanagh & Williams, 1982) as well as in swimming (Kipke, 1978; Swaine & Reilly, 1983). The aim of the prese~t study was to evaluate the dependence of blood lactate accumulation on 5 and d/ 5 during different swimming velocities and distances in female high-skilled swimmers.